ANALISIS YURIDIS AKTA KETERANGAN LUNAS YANG DIBUAT DIHADAPAN NOTARIS SEBAGAI DASAR DIBUATNYA KUASA MENJUAL - AHMAD JUARA PUTRA (PREMISE LAW JURNAL, 2016)
The implementation of the trade in the certified land title between the seller and the buyer can be done by making a PJB (Sale/Purchase Binding Agreement) on the land title. The research used judicial normative and descriptive analytic method. The research result shows that legal domicile of paying off certificate made before a Notary has authentic evidence for the buyer who has paid off the whole price of the certified land to the seller in a sale/purchase binding agreement on the certified land underhandedly. Keywords: Paying Off Certificate, Authority to Sell, Notary